Optimal timing of pacemaker implantation after cardiac surgery: should we wait 12 days? A 5-year observational study from a UK tertiary centre. (19th May 2022) - Tindale, A; Cantor, E; Cretu, I; Valli, H; Bhudia, S; Mason, M; Lane, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Purpose: Post-operative bradycardia is common but intrinsic rhythm often recovers. There is little consensus on the optimum time to wait between cardiac surgery and the implantation of a permanent pacemaker (PPM). Earlier device implantation may facilitate shorter length of stay. However, it may expose some patients who have no long-term pacing requirement to the risks associated with device therapy. This study aimed to understand how the number of days between cardiac surgery and PPM implantation is associated with pacing dependence and recovery of intrinsic conduction by 30 days. Methods: We examined healthcare records of consecutive patients who underwent cardiac surgery at our centre between 01/01/2015 to 01/01/2021. The primary outcome measures were pacing dependence (PD) at 30 days and recovery of intrinsic conduction at 30 days. Recovery was defined as showing evidence of intrinsic rhythm at the 30 day check after being pacing dependent at the time of implant. Patient demographics, baseline ECG characteristics and surgical procedure were recorded. Time to pacemaker implantation and pacing indication were identified. Pacing checks at 30 days post implant were reviewed and PD defined as no intrinsic rhythm seen over a 30 second period with base rate set at 40bpm. Univariate analysis and binary logistic regression were used to determine factors significantly associated with the primary outcome measures. Subsequent receiver-operator characteristic (ROC) analysis was used to determine the optimal timing of pacemaker implantation as defined by the Youden Index. This aims to maximise sensitivity and specificity of days to implant in predicting PD and conduction recovery at 30 days. Results: Following 5849 operations, 103 (1.8%) patients underwent PPM implantation for a new bradycardic indication. The baseline characteristics of those paced are summarised in table 1. Numerous factors were associated with pacing dependence at 30 days on univariate analysis (table 2). However, multivariate analysis showed that only PD at implant and days to implant (DTI) were significant predictors of PD at 30 days. The only significant association with conduction recovery was DTI. ROC analysis showed that the optimal DTI is 12 days for a variety of analyses: 1.) Predicting PD at 30 days for all patients (AUC 0.620, SE 0.056, p=0.031, 95% CI 0.511-0.730) 2.) Predicting PD in patients whose PPM indication was AV nodal dysfunction (AUC 0.706, p=0.001, Youden Index (YI) 1.34). 3.) Predicting recovery of intrinsic rhythm in patients who were pacing dependent at implant (AUC 0.80, p= 0.000, YI 1.515). Conclusions: The number of days between surgery and pacemaker implantation is the only factor significantly associated with both pacing dependence and recovery of intrinsic conduction at 30 days. The optimum time to wait is 12 days to allow time for intrinsic conduction to recover.